PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DANA ALOKASI KHUSUS, DAN DANA BAGI HASIL TERHADAP PENGALOKASIAN BELANJA MODAL PADA PEMERINTAH KOTA/KABUPATEN SE-JAWA BARAT TAHUN 2014 - Nugroho, Andreas Ell; Hardi, Meiril (JEA17: Jurnal Ekonomi Akuntansi, 2018)
ABSTRACTThe purpose of this study is to provide empirical evidence by using secondary data, regarding the effect of regional income, the general allocation fund and special allocation funds, revenue-sharing to the allocation of capital expenditures in municipalities/regencies in West Java in 2014. Samples used is a local government districts and cities in West Java as many as 26. The sampling technique is by engineering documentation. The method used in this research is descriptive analylis method. The data analysis technique used to test hypotheses include multiple linear regression, t test, F test, and R2 test. All the data acquired, processed using the test classical assumption of normality test, autocorrelation, multicollinearity test. In the classical assumption of normality test showed that the normal distribution of data, it is not free from the autocorrelation and multicollinearity.  So that the data did not deviate. Based on the results of statistical test tcalculate probability of PAD as big as 0,000 (p < 0,05), tcalculate probability of DBH as big as 0,844 (p > 0,05), tcalculate probability of DAU as big as 0,524 (p < 0,05), and tcalculate probability of DAK as big as 0,773 (p > 0,05). This suggests that the PAD significant effect on the allocation of capital expenditures. Whereas for the variable DBH, DAU and DAK no significant effect on the allocation of capital expenditure because it has significant value t > 0,05. Keywords: Regional income, revenue-sharing, the general allocation fund, a special allocation of funds and capital expenditure.